Association of circulatory Tfh-like cells with neutralizing antibody responses among chronic HIV-1 subtype C infected long-term nonprogressors and progressors. Issue 4 (23rd August 2019) - Swathirajan, Chinnambedu Ravichandran; Nandagopal, Pannerselvam; Vignesh, Ramachandran; Srikrishnan, Aylur Kailasam; Goyal, Rajat; Qureshi, Huma; Saravanan, Shanmugam; Solomon, Sunil Suhas; Hanna, Luke Elizabeth; Sivasankaran, Munusamy Ponnan; Singla, Nikhil; Mukherjee, Joyeeta; et al.
ABSTRACT: HIV-1 vaccine functioning relies on successful induction of broadly neutralizing antibodies (bNAbs). CXCR3− circulatory T-follicular helper (cTfh) cells are necessary for inducing B-cells for generating bNAbs. Recent studies have suggested that CXCR3+ Tfh cells might also influence bNAb production. Plasma samples from 34 ART-Naïve HIV-1 infected individuals [long-term nonprogressors (LTNP)—19; Progressors—13] were tested against a heterologous virus panel ( n  = 11) from subtypes A, B, C, G, AC, BC and AE. Frequencies of CXCR3+ and CXCR3− cTfh-like cells in peripheral circulation were studied using flow cytometry. LTNP showed significantly lower CXCR3+ and higher CXCR3− cTfh-like cell frequencies, while neutralization breadth was observed to be broader in progressors. A positive correlation was observed between bNAb breadth and potency with CXCR3+PD-1+ cTfh-like cells in LTNP. Based on neutralization breadth, 9 HIV-1 infected individuals were classified as 'top neutralizers' and 23 as 'low neutralizers' and they did not show any correlations with CXCR3+ and CXCR3− cTfh-like cells. These preliminary data suggest that CXCR3+ similar to CXCR3− might possess significant functional properties for driving B-cells to produce bNAbs. Hence, an HIV vaccine which is capable of optimal induction of CXCR3+ cTfh cells at germinal centers might confer superior protection against HIV. Abstract : This study addresses the correlation between Tfh subsets and breadth of neutralization in progressors and non-progressors HIV-infected individuals, showing a positive correlation between CXCR3+ Tfh cells and broadly neutralizing anti-HIV antibodies.